2021
DOI: 10.3389/fonc.2021.551160
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the EGFR Amplification and CDKN2A Deletion Regulated Transcriptomic Signatures Reveals the Prognostic Significance of SPATS2L in Patients With Glioma

Abstract: Purpose: This study was conducted in order to analyze the prognostic effects of epidermal growth factor receptor (EGFR) and CDKN2A alterations and determine the prognostic significance of EGFR and CDKN2A alterations on regulated genes in patients with glioblastoma (GBM) or lower grade glioma (LGG).Methods: The alteration frequencies of EGFR and CDKN2A across 32 tumor types were derived from cBioPortal based on The Cancer Genome Atlas (TCGA) datasets. The Kaplan–Meier analysis was used to determine the prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Through a series of experiments, spermatogenesis-associated serine-rich 2-like (SPATS2L) was confirmed as a downstream gene of miR-518a. SPATS2L is ubiquitously expressed in multiple tissues and its overexpression is related to the carcinogenesis of glioma and hepatocellular carcinoma [ 33 , 34 ]. Our results demonstrated that SPATS2L was upregulated in CDDP-resistant LSCC, and miR-518a inhibited SPATS2L expression by direct interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Through a series of experiments, spermatogenesis-associated serine-rich 2-like (SPATS2L) was confirmed as a downstream gene of miR-518a. SPATS2L is ubiquitously expressed in multiple tissues and its overexpression is related to the carcinogenesis of glioma and hepatocellular carcinoma [ 33 , 34 ]. Our results demonstrated that SPATS2L was upregulated in CDDP-resistant LSCC, and miR-518a inhibited SPATS2L expression by direct interaction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the most significant genes in each group were IDH1, which associates its mutated state with lower SHPK expression, and EGFR, which instead associates its mutated state with higher SHPK expression. This agrees perfectly with what we found in the literature, where strong evidence shows that IDH1 mutation is associated with a better prognosis for GBM patients [ 54 , 55 , 56 ], and on the other hand, EGFR mutation with a worse one [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…EGFR amplification was associated with the LUAD overall survival [ 51 ]. Similarly, LUAD with CCT6A amplification had poor progression-free survival contrast with LUAD without CCT6A amplification ( Figure 1(c) ).…”
Section: Resultsmentioning
confidence: 99%